Influence of lecithins on disorders of cognitive functions of animals caused by tetrachloromethane. - I. S. Svirgun; Mohammed Adab; O. S. Koshelev; O. L. Drozdov (Medičnì Perspektivi)
In our time the study of the influence of soya and especially sunflower lecithin as one of the natural monopolies inUkraine, on the state of cognitive functions is relevant. Specified neurotropic activity of lecithin is characterized by the obstacle to the development of behavioral manifestations of neurotoxic action of carbon tetrachloride, prevention of inhibition of mobility, research, unconditional reflex activity. In this article the determination of the effects of soy lecithin (L), and sunflower lecithin on a state of cognitive processes in rats showed that there is no significant differences between them. Changes in memory were judged by conventional passive-defensive reactions. Conditional reaction of passive avoidance (passive avoidance reaction) was produced on the basis of a single electric-skin support. We proposed modified method of assessing the presence of individually obtained memory trace and a group of genetically fixed form of memory. The establishment of this fact allows to make a comparative analysis of changes caused by the two lecithins in reproduction of individually obtainjed memory trace. Lecithin, derived from both plants in the conditions of intoxication by carbon tetrachloride prevents and improves reproduction of conditional reaction of passive avoidance. Soy lecithin and sunflower lecithin prevent the development of behavioral manifestations of neurotoxic action of carbon tetrachloride, preventing inhibition of mobility, research, unconditional reflex activity, cause expressive anti-amnesic effect contributing to the course of protective instinctive behavior in recognition of new circumstances as a safe. Both lecithins of plant origin exhibit the improving effect on the course of cognitive processes and their neuro-hormonal mechanisms in conditions of poisoning with carbon tetrachloride. Sunflower lecithin has more antidepressive, nootropic effect whereas soy lecithin has been demonstrated to have significant anti-amnestic effect.